Implementation of Event Management System Based on Campus Event Man-agement Information System As “Sistem Informasi Manajemen Acara Kampus” (SEMARAK) - Rizka Hadiwiyanti; Tri Lathif Mardi Suryanto; Nur Cahyo Wibowo (Nusantara Science and Technology Proceedings, 2020)
Within a year, Universitas Pembangunan Nasional "Veteran" East Java could hold dozens of conferences at the national or international level. A conference is a business event that prioritizes both internal communication and external communication. Several complaints regarding the preparation and execution of conferences and events are limited publications and promotion of events on campus for potential participants, the possibility of an insufficient number of participants when the event held, the lack of interaction between organizers and potential participants, and lack of coordination between the committee and campus facility providers. This research offers an implementation of the Campus Event Management Information System (SEMARAK) using the prototyping method as a solution. This research methodology starts with capture, convert, coordinate, deliver, and reporting. The first stage of system development builds the ability to publish campus events, schedule campus activity dates, and organize campus facility management. The system is expected to reduce the obstacles that occur during the preparation and execution of events on campus.